Do teachers leave the profession or move to another school when they don't fit?. Issue 4 (8th August 2017) - Vekeman, Eva; Devos, Geert; Valcke, Martin; Rosseel, Yves
Abstract: Teacher turnover is an international issue of continuing concern in education. While different antecedents of teachers' turnover intention have been identified, teachers' fit within the school (i.e. person-organisation [P–O] fit) in the context of turnover intention is still an emerging field of research. Building on the unfolding model of voluntary turnover, this study investigates the moderating role of teachers' perceived employability on teachers' P–O fit–job satisfaction–turnover intention relationship. Using survey data from 997 teachers across 74 schools, we conducted moderated mediation analysis. The analysis revealed different results for the hypothesised relationships depending on the specific dimension of turnover (i.e. intention to leave the profession or intention to move to another school). While P–O fit is directly related to the intention to move to another school, no evidence was found for a direct relation between P–O fit and the intention to leave the profession. Moreover, the results showed that the relation between P–O fit and the intention to leave/intention to move is mediated by job satisfaction. Yet, only for intention to leave, a small but significant moderating effect of perceived employability was found. These findings provide insight into the psychological processes of teachers wanting to leave the teaching profession or move to another school. Limitations, suggestions for further research and implications are also discussed in this article.